2012
DOI: 10.1017/s1461145711001945
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter occupancy with TCAs and SSRIs: a PET study in patients with major depressive disorder

Abstract: The aim of the present clinical positron emission tomography study was to examine if the 5-HTT is a common target, both for tricyclic antidepressants (TCAs) and selective serotonin reuptake inhibitors (SSRIs). Serotonin transporter (5-HTT) occupancy was estimated during treatment with TCA, SSRI and mirtazapine in 20 patients in remission from depression. The patients were recruited from out-patient units and deemed as responders to antidepressive treatment. The radioligand [11C]MADAM was used to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 25 publications
1
40
0
1
Order By: Relevance
“…Following SSRI administration, the drugs are thought to increase extracellular serotonin concentrations by serotonin transporter (SERT) inhibition. Positron emission tomography (PET) studies using SERT-selective radioligands have demonstrated a reduction in striatal radioligand binding of about 64-72 % after a single escitalopram or citalopram dose (Baldinger et al 2014;Lanzenberger et al 2012;Lundberg et al 2007) and of 60-80 % in MDD patients during at least 3 weeks of escitalopram or citalopram treatment (Baldinger et al 2014;Herold et al 2006;Lanzenberger et al 2012;Lundberg et al 2012;Meyer et al 2004;Smith et al 2011). As the antidepressant action of SSRI treatment is delayed by several weeks, downstream effects, such as desensitization of presynaptic autoreceptors, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Following SSRI administration, the drugs are thought to increase extracellular serotonin concentrations by serotonin transporter (SERT) inhibition. Positron emission tomography (PET) studies using SERT-selective radioligands have demonstrated a reduction in striatal radioligand binding of about 64-72 % after a single escitalopram or citalopram dose (Baldinger et al 2014;Lanzenberger et al 2012;Lundberg et al 2007) and of 60-80 % in MDD patients during at least 3 weeks of escitalopram or citalopram treatment (Baldinger et al 2014;Herold et al 2006;Lanzenberger et al 2012;Lundberg et al 2012;Meyer et al 2004;Smith et al 2011). As the antidepressant action of SSRI treatment is delayed by several weeks, downstream effects, such as desensitization of presynaptic autoreceptors, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Developments of novel treatments are hampered by a limited understanding of the pathophysiology underlying MDE. Using positron emission tomography (PET), our group and others have shown in the living human brain of both control subjects and patients with depressive episodes that for most antidepressant drug treatments the mechanism of action involves inhibition of the serotonin (5‐HT) transporter (5‐HTT) and in some cases also the norepinephrine transporter . With established antidepressant treatment only two‐thirds of patients with major depression achieve remission …”
mentioning
confidence: 99%
“…Using positron emission tomography (PET), our group and others have shown in the living human brain of both control subjects and patients with depressive episodes that for most antidepressant drug treatments the mechanism of action involves inhibition of the serotonin (5-HT) transporter (5-HTT) and in some cases also the norepinephrine transporter. [2][3][4][5] With established antidepressant treatment only two-thirds of patients with major depression achieve remission. 6 The dopamine (DA) system has been suggested to be involved in the pathophysiology of MDE.…”
mentioning
confidence: 99%
“…The most commonly used antidepressants besides SSRIs, for example, serotonin‐norepinephrine reuptake inhibitors and tricyclic antidepressants also have an inhibitory effect on presynaptic reuptake inhibition of serotonin in PLTs, which might explain the observed additive effect . This could indicate a dose–response relationship resulting in different transfusion rates caused by various levels of exposure to drugs that inhibit reuptake of serotonin in PLTs, although this mechanism is not well described …”
Section: Discussionmentioning
confidence: 94%